Peran Mahasiswa KKN UNP dalam Pembuatan Papan Edukasi Waktu Terurai Sampah di Nagari Jawi-Jawi Guguk - Refa Olivia Andani; Meira Marini; Rima Anjeli; Nia Rahmada Yani; Maroatul Nazifah; Suci Ramadhani; ⁠Nazwa Edia; Sahuradhano rise (CV. ITTC INDONESIA, 2026)
Waste management remains an environmental issue that requires serious attention due to the increasing volume of waste and the low level of public awareness regarding its long-term impacts on the environment. One effort to enhance environmental awareness is through educational media. Visual-based educational media that are easy to understand and can be utilized sustainably, such as a Waste Decomposition Time Educational Signboard, can serve as an effective educational tool. This program aimed to improve public understanding and awareness of the decomposition time of various types of waste in Nagari Jawi-Jawi Guguak, Gunung Talang District, Solok Regency, West Sumatra. The activity was carried out by students of the Community Service Program (KKN) of Universitas Negeri Padang (UNP) as a form of community engagement. The implementation methods included field observation, identification of environmental issues, design of educational media, signboard production, and installation of the signboard at strategic locations easily accessible to the community. The educational signboard provided information on different types of waste and their estimated decomposition periods in the environment. The results indicated that the educational signboard served as an attractive source of information and contributed to increasing public knowledge about the importance of proper waste disposal and waste segregation. Furthermore, the visual media placed in public spaces was considered effective as a long-term educational tool for fostering environmentally responsible behavior. Therefore, the waste decomposition time educational signboard program can serve as an initial step in supporting the creation of a clean, healthy, and sustainable environment.